2008
DOI: 10.1186/1471-2334-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of pneumococci obtained from Gambian children aged 2–29 months with invasive pneumococcal disease during a trial of a 9-valent pneumococcal conjugate vaccine

Abstract: Background: The study describes the molecular epidemiology of Streptococcus pneumoniae causing invasive disease in Gambian children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…Further, comparison of our strains with those in the global pneumococcal MLST database resulted in the classification of 45 strains into 20 CCs and 5 singletons, thus confirming the high diversity within the global pneumococcal MLST database. Results of several studies performed in different countries also indicate high-level heterogeneity among the pneumococcal population (5,9,17,18). Turkish strains also show very heterogeneous global distribution (20).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, comparison of our strains with those in the global pneumococcal MLST database resulted in the classification of 45 strains into 20 CCs and 5 singletons, thus confirming the high diversity within the global pneumococcal MLST database. Results of several studies performed in different countries also indicate high-level heterogeneity among the pneumococcal population (5,9,17,18). Turkish strains also show very heterogeneous global distribution (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that isolates within the same clone express different capsular serotypes because of the natural transformation of pneumococcal DNA (9,18,21). This phenomenon (called capsular switching) results in the emergence of a clone with a different capsular type (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations